The use of autologous skeletal muscle-derived cells as a sling in the treatment of stress-induced urinary incontinence: An experimental study in dogs - Wadie, Bassem S.; Aamer, Haytham G.; Khater, Sherry M.; Gabr, Mahmoud M. (Frontiers in Urology, 2023)
Purpose:‎ This is an experimental preclinical study testing the applicability of ‎autologous skeletal muscle-derived cells as a treatment of SUI in a canine ‎model.‎ Methods:‎ Ten mongrel dogs were included in this study. Skeletal muscle was ‎harvested for biopsy in 4 dogs. One month later, incontinence was induced ‎in 8 dogs through urethrolysis. Biopsied muscle cells were incubated and ‎expanded for 8 weeks. Muscle-derived cells were collected and covered ‎with a polyglycolic acid (PGA) scaffold immersed in culture medium and ‎coated with Matrigel to be used as a sling, which was placed suburethrally ‎in 8 dogs; 4 had cell seeding, and 4 had scaffolds only. Urethral pressure ‎‎(UP) measurements were performed at baseline and 2 & 6 weeks after sling ‎insertion. The urethra was harvested 4 weeks after sling insertion for ‎histopathology.‎ Results:‎ UP showed an increase in maximum urethral pressure during static ‎measurement in all dogs with a scaffold inserted. The increase ranged from ‎‎5-40 cmH2O. Histopathology showed significant periurethral proliferation ‎of skeletal muscles in 4 dogs with cell-seeded scaffolds. These levels were ‎the maximum levels in dogs # 1 & 2. This was not the case in the 4 dogs ‎that had slings only.‎ Conclusion: The use of skeletal muscle-seeded PGA scaffolds is a practical ‎technique with preserved histological differentiation integrity in a canine ‎model.‎